PENGARUH KETERAMPILAN SOSIAL TERHADAP HASIL BELAJAR SISWA BERKEBUTUHAN KHUSUS DI SDN 2 WRINGINANOM KAB. GRESIK - Afifah Afifah (Jurnal Keislaman, 2021)
Every citizen has the same right to obtain quality education. Even citizens whohave physical, emotional, mental, intellectual or social disabilities are also entitled toeducation even though they have to go through special education. With the existence of thisstudy aims to determine the social skills of students with special needs in SDN 2WringinomKab. Gresik, to find out the learning outcomes of students with special needs atSDN 2 WringinomKab. Gresik, and to find out how the influence of social skills on thelearning outcomes of students with special needs at SDN 2 WringinomKab. Gresik The typeused in this research is quantitative research, in this case the researcher uses independentcorrelation to look for relationships and test hypotheses between two or more variables. Theobject of asdalah research at SDN 2 Wringinom district. Gresik, researchers used productmoment correlation techniques. The data collection techniques the methods that researchersuse are observation, questionnaire and documentation, while for data analysis techniquesusing descriptive analysis and Inferential analysis. Hopefully with this research the teachershould increase student confidence (self-efficacy) so that students with special needs feelconfident in their potential and are able to complete their learning tasks as well as possible,and further researchers should conduct research on other aspects because there are manyother aspects / factors that affect ABK student learning outcomes.